2012
DOI: 10.4049/jimmunol.1002612
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Tolerance to a Tumor Antigen Encoded by a Cancer-Germline Gene

Abstract: Central tolerance toward tissue-restricted Ags is considered to rely on ectopic expression in the thymus, which was also observed for tumor Ags encoded by cancer-germline genes. It is unknown whether endogenous expression shapes the T cell repertoire against the latter Ags and explains their weak immunogenicity. We addressed this question using mouse cancer-germline gene P1A, which encodes antigenic peptide P1A35–43 presented by H-2Ld. We made P1A-knockout (P1A-KO) mice and asked whether their anti-P1A35–43 im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…However, P1A-deficient mice demonstrated enhanced P1A-specific T cell responses and increased tumor protection from P1A-expressing P815 tumor cells. Furthermore, TCR-Vβ usage of P1A-specific T cells was slightly altered, suggesting that ectopic expression of P1A during thymic development skews the peripheral T cell repertoire [55]. These results and others support a role for central tolerance in limiting, not eliminating, T cell responses against self-antigens [56, 57].…”
Section: Central Tolerancementioning
confidence: 72%
See 1 more Smart Citation
“…However, P1A-deficient mice demonstrated enhanced P1A-specific T cell responses and increased tumor protection from P1A-expressing P815 tumor cells. Furthermore, TCR-Vβ usage of P1A-specific T cells was slightly altered, suggesting that ectopic expression of P1A during thymic development skews the peripheral T cell repertoire [55]. These results and others support a role for central tolerance in limiting, not eliminating, T cell responses against self-antigens [56, 57].…”
Section: Central Tolerancementioning
confidence: 72%
“…Mice deficient in gp70 are more resistant to CT26 tumor challenge, and their CD8+ T cells following immunization with the AH1 peptide display increased staining intensity with the AH1-H-2L d multimers, suggestive of a higher avidity T cell response [54]. Huijbers et al [55] recently demonstrated similar results using the non-mutated cancer–testis antigen P1A from the mastocytoma tumor P815. Functional CD8+ T cell responses following vaccination with the H-2L d -restricted P1A 35–43 epitope are detectable in DBA/2 mice that express P1A in the thymus, suggesting incomplete central tolerance to this antigen.…”
Section: Central Tolerancementioning
confidence: 95%
“…We have specifically focused on SSX2, which we found is expressed in ~25% of metastatic prostate cancer lesions [18], and immune responses to which we have observed in patients with prostate cancer [14,17]. As a CTA this protein likely has limited central tolerance since its expression in normal tissues is restricted to immune-privileged testis tissue [19]. We previously identified two HLA-A2-restricted SSX2 epitopes (p41–49 and p103–111), T cells specific for which can lyse SSX2-expressing prostate cancer cells, and we demonstrated that HLA-A2 transgenic mice immunized with a DNA vaccine encoding SSX2 develop p41–49- and p103–111-specific T cells [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Aire deficient mice may have increased memory response to melanoma following immunization with irradiated melanoma cells (19). At the same time, however, recent work also suggests that thymic expression of a cancer-germline antigen only minimally changes T cell responses to antigen-expressing tumors (20). Additionally, Aire-regulated thymic expression of tyrosinase, a shared vitiligo/melanoma antigen, does not shape the tyrosinase-specific T cell repertoire (21).…”
Section: Introductionmentioning
confidence: 99%